Assessment of Megaphrynium Macrostachyum (Benth & Hook) Planting Materials in Kisangani, D.R.Congo - Mokikima, Louis; Litucha, L, Joseph; Ngama, Faustin; Nzawele, Dowiya B.; Okungo, Albert (Budapest International Research in Exact Sciences (BirEx) Journal, 2024)
This study aimed to contribute to the domestication of Megaphrynium macrostachyum by identifying the planting materials in order to avoid its disappearance, due to forests anthropic pressure. Planting trial of this forest plant species (M macrostachyum) in relation to propagation materials was established in two sites (Kisangani and Abunakenge), in order to identify the best propagation method for its cultivation which poses fewer problems of seed germination and regular of rhizome fragments sprout, survival rate as well as juvenile plants growth. The results demonstrated that, M. macrostachyum seeds were generally characterized by embryonic dormancy, thus leading to very late germination ranging from 6 to 7 months; while rhizome fragments present fewer sprout problems (1 to 2 months). Cuttings (rhizome fragments) proved to be the most suitable propagating material for M. macrostachyum cultivation, because it poses fewer sprout problems. However, its generative multiplication (seeds) is also possible, only there is a dormancy problem that need to be resolved.